COGENERATION AND TRIGENERATION SYSTEMS - Marčič, Simon (Journal of Energy Technology, 2024)
This paper describes a cogeneration plant using wood biomass as fuel. Forests cover 56% of the surface area in Slovenia, providing plenty of waste wood to be used as an energy source. Waste wood unsuitable for the lumber industry is ground into biomass of G50 size, which are chips of, measuring on average 3–5 cm and up to 8 cm. Biomass is dried in a drier to reduce its moisture content to 15%. Wood biomass gasification takes place in a gasifier. Carbon monoxide and hydrogen, gasification end products, are used as fuels for a boiler and two gas engines. The boiler heat is used for wood-drying purposes. The cogeneration plant uses a 1 MW Caterpillar generator set and a 0.45 MW MAN generator set. Cooling water waste heat of both gas engines and exhaust gases are used for heating the wood drier and the nearby residential area.